Characteristics of PVDF Membranes Irradiated by Electron Beam - Jaleh, Babak (Membranes (Basel), 2015)
Polyvinylidene fluoride (PVDF) membranes were exposed vertically to a high energy electron beam (EB) in air, at room temperature. The chemical changes were examined by Fourier Transform Infrared Spectroscopy (FTIR). The surface morphologies were studied by Scanning Electron Microscopy (SEM) and showed some changes in the pore size. Thermogravimetric (TGA) analysis represented an increase in the thermal stability of PVDF due to irradiation. Electron paramagnetic resonance (EPR) showed the presence of free radicals in the irradiated PVDF. The effect of EB irradiation on the electrical properties of the membranes was analyzed in order to determine the dielectric constant, and an increase in the dielectric constant was found on increasing the dose. The surface hydrophilicity of the modified membrane was characterized by water contact angle measurement. The contact angle decreased compared to the original angle, indicating an improvement of surface hydrophilicity. Filtration results also showed that the pure water flux (PWF) of the modified membrane was lower than that of the unirradiated membrane.